Overcoming the welfare state. Local safety policies in the venetian area - Vianello, Francesca (Universidad Nacional de Quilmes, 2003)
This article intends to describe a process of transformation recently affecting the whole Europe. It is the progressive overcoming of welfare State traditionally meant as garantuee for all citizens of the essential services for their own subsistence and wellbeing allocated on the basis of the principles of universality, solidarity and equity. Since it is a process that largely affects all social policies, we have thought it right to choose a definite visual angle from which to observe from closer the evolution and strenghtening of the neoliberist trends. We have choosen the visual angle of security itended as a public good, the substanzial definition of which appears to be profoundly linked to the idea of the State and society to which it refers. Our starting point is the passage from an attitude of concern linked to the topic of public order to a diffuse sense of alarm related to the urban security. This shift has been underlined by several authors. In the public communication, this shift can be seen as a changing point of observation: the general accountability of the central State in managing its citizens security has been, or at least can be, replaced by that of the local communities. Therefore our interest has moved to the local contents that are often characterizing the traditional theme of public safety, especially in relation with the different strategies of prevention and security. It is in fact in the tension between a preventive and a repressive point of view that we can foresee the possibility of a real change, tied to the local dimensions of the new security projects.